Legal Protection Of Well-Known Trademarks Under Indonesian Law - Windiantina, Wiwin; Nurastriani, Neneng (Constitutionale, 2024)
This research evaluates the legal protection of famous trademarks under Indonesian law, examining the extent to which existing regulations safeguard trademarks with strong public recognition. As valuable corporate assets, famous trademarks require effective legal protection to prevent misuse and infringement. However, globalization and technological advancements have intensified intellectual property violations, posing significant challenges to trademark owners. Using a normative juridical approach, this research analyzes relevant legislation and judicial practices in Indonesia while identifying obstacles in maintaining trademark exclusivity in both domestic and international markets. Through this analysis, the research aims to provide policy recommendations to strengthen trademark protection and develop a more adaptive legal framework that responds to technological and global challenges.